Phase transitions in monoglyceride bilayers. A light scattering study. - Crawford, G E (1986)
Thermotropic phase transitions in single planar bilayers of glycerol mono-oleate have been investigated using quasi-elastic light scattering from thermally excited membrane fluctuations. In certain cases both spectroscopic and intensity information were derived from the observations. For solvent-free bilayers transitional changes were observed in several membrane parameters: in tension, viscosity and thickness, in a combination of lipid orientational order parameter and dielectric anisotropy, and in the lateral compression modulus. These changes, particularly those in membrane thickness and in the anisotropy/order combination, were clearly indicative of a chain-melting transition in the lipid molecules. The chain-melting transition temperature was identified as 16.6 +/- 0.03 degrees C (delta T 1/2 = 1.5 degrees C). The other changes tended to cluster around 12.5 and 16.6 degrees C, suggesting that a two-stage transition was involved. Analysis of pretransitional fluctuations in membrane viscosity, based on a Landau approach, suggested that at the transition the membrane was close to a critical point (T = 12.7 degrees C). Less information was accessible for membranes containing n-decane within their structure. In this case, the change in membrane tension was much smaller than in the solvent-free case and the transition was considerably broadened. These effects accord with an increase in 'interactive volume' within the bilayer due to solvent inclusion.